Dampak Dana Alokasi Khusus Pertanian dan Irigasi Terhadap Produksi Padi Sawah dan Ketahanan Pangan Kabupaten/Kota di Provinsi Jambi - Zainuddin Zainuddin (Jurnal MeA (Media Agribisnis), 2021)
How important is the impact of special allocation funds (DAK) on agriculture and irrigation as policy input in food production and food security in the regions. To answer these problems, a study was conducted with the objectives of: 1) formulating an economic model for lowland rice commodity related to the financing of special allocation funds (DAK) for agriculture and irrigation in Jambi Province; and 2) analysis of the impact of funding for the special allocation fund (DAK) for agriculture and irrigation on the area of irrigation, rice fields and food security in districts / cities in Jambi Province. The simulation results show that an increase in the supply of financing from special allocation funds (agriculture and irrigation) can have a positive impact on increasing resources (irrigation area), food production, and regional food security. In order to be more effective in allocating funds, it is advisable to synergize with the allocation of subsidized fertilizers and seeds in each district / city in Jambi Province. Besides being aimed at maintaining and repairing irrigation networks in several districts / cities, the DAK irrigation program needs to be expanded to develop small - medium scale irrigation models for potential wetlands (rainfed, swamp, tidal) for the production of rice and other food crops. The potential available land types require a suitable location-specific technology package for rice and other food crops. Likewise, the use of cheaper alternative inputs. Reorientation of programs funded by DAK for agriculture in each district / city in Jambi province is needed to achieve effectiveness and impact on increasing lowland rice production and food security in the regions.Keywords: Allocation Funds, Food Security, Irrigation, Paddy, Simultaneity Model